2013
DOI: 10.3354/esr00547
|View full text |Cite
|
Sign up to set email alerts
|

Using observed seabird fallout records to infer patterns of attraction to artificial light

Abstract: Attraction of fledgling shearwaters, petrels, and storm-petrels to artificial light has been documented for decades on islands around the world and is considered a significant threat to many species. Although large numbers of downed birds have been observed after being disoriented by light, several important elements of this 'fallout' phenomenon are unknown, including the locations along the path from nest to ocean at which attraction and/or disorientation occurs and whether fledglings can be attracted back to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
38
1
2

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(42 citation statements)
references
References 21 publications
1
38
1
2
Order By: Relevance
“…Efforts to model the spatial fallout distribution generally show positive relationships with light pollution levels taken from satellite imagery (Rodrigues et al ; Troy et al. , ). The spatial distribution of breeding colonies and their proximity to lit areas (directly adjacent or on transit routes out to sea) also plays a crucial role in determining the severity of the light‐induced impact on seabirds.…”
Section: Temporal and Spatial Distribution Of Falloutmentioning
confidence: 99%
See 2 more Smart Citations
“…Efforts to model the spatial fallout distribution generally show positive relationships with light pollution levels taken from satellite imagery (Rodrigues et al ; Troy et al. , ). The spatial distribution of breeding colonies and their proximity to lit areas (directly adjacent or on transit routes out to sea) also plays a crucial role in determining the severity of the light‐induced impact on seabirds.…”
Section: Temporal and Spatial Distribution Of Falloutmentioning
confidence: 99%
“…In some cases, this type of attraction may be a large proportion of total fallout on the island (Troy et al. ). However, tracked flights of Cory's Shearwater fledglings from nests to grounding locations suggest birds were grounded on the night they fledge and very close to their natal burrows (Rodríguez et al.…”
Section: Temporal and Spatial Distribution Of Falloutmentioning
confidence: 99%
See 1 more Smart Citation
“…One major group influenced by artificial light pollution comprises birds that show nocturnal activity, such as petrels and shearwaters (family Procellariidae; Rodr ıguez et al 2017). Recent studies have found that seabirds are more likely to be encountered in locations with high light intensity (Le Corre et al 2002, Rodr ıguez & Rodr ıguez 2009, Rodrigues et al 2012, Troy et al 2013, Rodr ıguez et al 2015. Fledglings on their first flight are often found to crash-land in the cities and towns near their nest-sites; this phenomenon can be termed 'grounding' (Le Corre et al 2002, Rodr ıguez et al 2014 or 'fallout' (Ainley et al 2001, Troy et al 2011.…”
mentioning
confidence: 99%
“…Nocturnal artificial lighting on vessels has been shown to disorientate seabirds, particularly fledglings, leading to "fallout, " in which the birds fly toward the light source and become exhausted or collide with man-made objects (Troy et al, 2013). Research is needed to determine the extent to which Beck's petrel (Pseudobulweria becki)-a species listed as critically endangered on the International Union for the Conservation of Nature Red List and which is native to Papua New Guinea and the Solomon Islands-would be attracted by artificial light used in proposed mining operations.…”
Section: Anthropogenic Lightmentioning
confidence: 99%